As projeções do avanço em saúde mental nos casos de tabagismo, álcool e violência doméstica no cenário pandêmico da covid-19: uma revisão sistemática da literatura - Correa, Jailda de Souza (2021)
Introduction: The announcement of a new pandemic called SARS-CoV-2 responsible for causing Covid-19 disease and the time needed to combat it is short. In a short period of time people become ill and die. Quarantine has been established and a measure of social isolation has also been adopted, classified as of paramount importance by the World Health Organization - WHO for combating community transmission of the SARS-CoV-2 virus by mitigating the growth in numbers of people infected at the same time. Objective: The objective is to verify and analyze the projections of the advance of smoking, alcohol and domestic violence in the period of social isolation. Methodology: This is a systematic review of the literature with pre-defined steps, with the methodological path guided in the construction of a protocol as a guide for the research. Results: From the 7 selected articles, there is a prevalence of tobacco and alcohol use and violence against women in relation to the period of social isolation. Conclusion: It concludes that the adverse effects of social isolation and quarantine, triggered a increase in the use of tobacco, alcohol and domestic violence behavior.